ASCT1 and ASCT2: Brother and Sister?. (October 2021) - Scalise, Mariafrancesca; Console, Lara; Cosco, Jessica; Pochini, Lorena; Galluccio, Michele; Indiveri, Cesare
The SLC1 family includes seven members divided into two groups, namely, EAATs and ASCTs, that share similar 3D architecture; the first one includes high-affinity glutamate transporters, and the second one includes SLC1A4 and SLC1A5, known as ASCT1 and ASCT2, respectively, responsible for the traffic of neutral amino acids across the cell plasma membrane. The physiological role of ASCT1 and ASCT2 has been investigated over the years, revealing different properties in terms of substrate specificities, affinities, and regulation by physiological effectors and posttranslational modifications. Furthermore, ASCT1 and ASCT2 are involved in pathological conditions, such as neurodegenerative disorders and cancer. This has driven research in the pharmaceutical field aimed to find drugs able to target the two proteins. This review focuses on structural, functional, and regulatory aspects of ASCT1 and ASCT2, highlighting similarities and differences.